Curves According to the Successor Frame in Euclidean 3-Space - Melek Masal (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thepresent study, the successor formulae of the successor curves defined byMenninger [1] are given. Then, by defining the successor planes, the geometricmeanings of the successor curvatures are investigated and the relations acrossthe components of the position vectors of successor curves are found.Furthermore, in this study, it is proven that lies in the 3rd.type successorplane, lies in the 1st type successorplane and by defining the involute-evolute S-pair, the distance between thecorresponding points of these curves is found.